Application of extended theory of planned behavior to predict intention in food safety practices among adult consumers in Sibu, Sarawak, Malaysia - Ruby, Genevie Eleanor (2020)
Foodborne disease (FBD) is a global problem that also occurred in Malaysia. Despite various efforts, food poisoning cases continue to show an increment. This case is not only occurred at food premises but also reported at home. Recognizing this, adult consumers who handle food at home should even know and adhere to the practice of food safety. It was also essential to examine the relationship between a sociodemographic profile and factors that influence the level of food safety knowledge and self-reported practices. In this study, the corporation of food safety knowledge to extend the Theory of Planned Behavior (TPB) was attempted to explain the factors affecting intention on safe food handling. The moderating effect of gender and educational level on the relationship between TPB factors and intention was also determined. The cross-sectional survey by using self-administered questionnaires was carried out for hypothesis testing. A total of 623 adult consumers aged 20 and above participated in this study and were selected using convenience sampling. The descriptive analysis showed that food safety knowledge was good even though the selfreported practices had been unsatisfactory. The analysis using one-way ANOVA and independent sample t-test showed that both food safety knowledge and self-reported practices were significantly different based on gender, education level, number of children in the family, and frequency of food preparation at home. Meanwhile, the result of logistic regression indicated that education level (p = 0.00) were the most reliable predictor for food safety knowledge level while gender (p = 0.00) is the main contributor to self-reported practices. The Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to evaluate the measurement model and structural model of extended TPB. The assessment of measurement model was meet the requirement for convergent (Overall factor loading>0.60, AVE>0.5, CR>0.7) and discriminant validity (HTMT ratio<0.850). The result structural model revealed that attitude, subjective norm, and perceived behavior control had a positive and significant effect towards intention on safe food handling. Moreover, the subjective norm was the main predictor of consumer safe food handling intention (β = 0.418, R² = 0.337, Q² = 0.252, p < .05). As such, the role of the family to promote safe food handling at home is evident. Food safety knowledge also had a positive impact on consumer's attitude (β = 0.107, R² = 0.012, Q² = 0.004, p < .05). Based on the result of multi-group analysis it indicated that only educational level significantly moderates the relationship between perceived behavior control and intention of safe food handling (p = 0.02). However, there was no significant moderating effect of attitude (p = 0.286) and subjective norm (p = 0.070). The results attained from the analyses produced a model that predicts the intention of safe food handling among consumers including the factor that moderate it. Several implications were also depicted from the findings of this study. Therefore, this study has contributed to the existing knowledge in food safety and facilitates the exploration of future research focusing on consumers that handle food at home.